Political Marketing-Based Political Communication Strategy in the 2024 Bandung City Election: A Case Study of Muhammad Farhan And Erwin's Winnings - Sarah Pamela (Jurnal Dialektika: Jurnal Ilmu Sosial, 2026)
This study analyzes the political communication strategies implemented by the Muhammad Farhan and Erwin ticket in the 2024 Bandung City Regional Election using a political marketing perspective. In the context of modern electoral democracy, political communication is no longer understood solely as a campaign activity, but rather as a strategic process that is voter-centered and designed to respond to public needs and preferences. This study uses a qualitative approach with a case study method, with data collection techniques through document analysis, literature review, and secondary data collection sourced from mass media, social media, electability survey results, and official publications of related institutions. The results show that the success of the Farhan-Erwin ticket is influenced by the implementation of an integrated political marketing strategy, including the use of social media as the main arena for political communication, the use of political branding through the slogan "Bandung Utama", and the involvement of community leaders as opinion leaders in expanding communication reach. This strategy reflects a shift from a candidate-centric campaign approach to a voter-oriented approach, especially the millennial generation and Generation Z. In addition, the research findings show that success in the media arena contributes significantly to increasing electability in the electoral arena. This study concludes that an effective political communication strategy in regional elections (Pilkada) is determined not only by campaign intensity, but also by the candidate's ability to integrate communication, political branding, stakeholder management, and voter orientation within an adaptive political marketing framework. These findings provide theoretical and empirical contributions to the development of political communication and political marketing studies in the context of regional head elections in Indonesia